Thrombolysis in Real Time: Demonstration of Revascularization with Intravenous Thrombolysis Therapy in the CT Scanner. Issue 1 (21st September 2016) - Tan, Jessica; Aysenne, Aimee; Singh, Vineeta
ABSTRACT: BACKGROUND AND PURPOSE: Administration of intravenous tissue plasminogen activator (tPA) in the computed tomography (CT) scanner has been recently implemented at our institution, as a means to decrease door‐to‐needle time. This change in protocol provided us a unique opportunity to visualize imaging signs of early recanalization. METHODS: We evaluated patients who presented with acute ischemic stroke both before and after a change in protocol for intravenous tPA administration. We identified 10 patients who received tPA on the CT scanner and 22 patients who received tPA after CT imaging was complete. Early recanalization was defined as distal migration of thrombus or disappearance of thrombus between initial phases of imaging, large territory of diminished mean transit time on initial perfusion CT, large territory of increased cerebral blood flow on initial perfusion CT, and/or large territory of increased cerebral blood volume on initial perfusion CT. Late recanalization was defined as distal migration of thrombus or disappearance of thrombus between initial and follow‐up imaging, decreased attenuation of thrombus between initial and follow‐up imaging, or infarcted territory on follow‐up imaging smaller than the cerebral blood volume defect on initial perfusion CT. RESULTS: In the patients who received tPA on the CT scanner, 20% demonstrated imaging evidence of early recanalization and 30% demonstrated imaging evidence of late recanalization. In the patients who received tPA after CT imaging, 57% demonstrated imaging evidence of late recanalization. CONCLUSION: Early recanalization of large‐vessel occlusion after intravenous thrombolysis results in unique imaging findings.